Clinical-epidemiological profile of patients with pressure injuries in the hospital context (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: describe the clinical-epidemiological profile of patients with pressure injuries admitted to a university hospital. Method: descriptive study with 122 patients with pressure injuries admitted to a university hospital between January 2018 and December 2019. Data were collected from patients’ medical records and from the Serviço Assistencial de Cuidados com a Pele (Skin Care Assistance Service) database. Descriptive statistics were used for data analysis. Results: pressure injuries predominated among adults and the elderly, browns, who studied up to elementary school and had no partner. There was a similarity between the sexes. The patients had, mainly, infectious disease, one or more comorbidities, nutritional alteration, mixed incontinence and used nutritional therapy, but did not present dermatitis associated with incontinence and smoking history. Most patients were classified as high risk of pressure injury. The study totaled 237 lesions, most of which were acquired before admission, not classifiable, located in the sacrococcygeal region, treated topically with hydrogel with alginate and hydrocolloid, and not healed at the time of hospital discharge. Conclusion: the studydescribed important aspects of the characterization of pressure injuries, as well as the people affected by this serious health problem, which can optimize prevention and treatment actions.